Tecnologias digitais da informação e da comunicação e produção de textos dissertativo-argumentativos no ensino médio : da sistematização de buscas ao desenvolvimento da criticidade - Rabelo, Barbara Helena (2017)
The present study focuses on the use of digital tools as an aid to improve the criticality in Writing. The aim of this study is to investigate the extent to which the use of Information and Communication Technologies (ICTs) - specifically the Padlet tool - can be used as a way to improve the students' criticality on Writing intheir mother tongue, a desired result at the end of their school years (Law 9.394 / 96). We used the educational resources offered by this tool in order to expose the student to other people‟s opinions and points of view, aiming the student would be more aware of his own opinion and this way develop a more critical opinion himself of the facts surrounding him. The theoretical framework was based on two themes: the use of digital tools in education and the critical literacy. The digital tools are conceived as tools for students to expand their reading possibilities through the use of the Internet, which gives them access to new ideas, new texts and ultimately, new ways of reading (BRAGA; MORAES, 2010; LEMKE, 2012). Considering the student as a social and historical person (SOUZA, 2011) and the interpersonal aspect of the language (BAKHTIN, 1992), we understand criticality as the possibility of a person to see the world coming out of their own bias, seeing beyond other people‟s point of view. Based on this concept of criticality, we developed steps to detect evidences of criticality in students' Writings. For this study, we had the collaboration of thirty-five Senior year students of a private High School in Patrocínio-MG, where the teacher-researcher works. In this qualitative research study (LÜDKE and ANDRÉ, 1986), the data was collected through two questionnaires, teacherresearcher‟ s notes, Padlets made by students and Writings having the Padlet as the main resource. As a result, we noticed the use of other points of viewbesides their own in the student‟s Writing, either to confirm or refute their own thoughts as well as express their own reflective opinions, revealing this way the use of criticality in different levels in their Writing and also the validation of the use of the proposed tool, the Padlet.